2017
DOI: 10.1111/1460-6984.12351
|View full text |Cite
|
Sign up to set email alerts
|

Teacher–child relationships and classroom‐learning behaviours of children with developmental language disorders

Abstract: These results suggest that the quality of the teacher-child relationship for children with DLDs during preschool is associated within their learning-related behaviours in the classroom both concurrently and in the subsequent year. Findings suggest that teacher-child relationships should be explored as a mechanism for improving the learning-related behaviours of children with DLDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 88 publications
(184 reference statements)
1
10
1
Order By: Relevance
“…Factors influencing the education of preschool children with developmental speech and language disorders are a set of "perinatal, medical and environmental variables" that determine "speech and language outcomes" in the future. The level of education of parents is an additional factor in the effectiveness of education and the level of humanization of education (McAllister, L., et al, 1993;Rhoad-Drogalis, A., et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Factors influencing the education of preschool children with developmental speech and language disorders are a set of "perinatal, medical and environmental variables" that determine "speech and language outcomes" in the future. The level of education of parents is an additional factor in the effectiveness of education and the level of humanization of education (McAllister, L., et al, 1993;Rhoad-Drogalis, A., et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Children's attention/persistence was consistently related to TSE, whereas competence-motivation and learning strategies showed fewer associations to TSE. While no prior studies have examined whether children's learning behaviors predict TSE, previous findings indicate that TSE predicts children's learning behaviors (Reyes et al, 2012;Rhoad-Drogalis et al, 2018;Ross et al, 2001). In regard to attention/persistence, Rhoad-Drogalis and colleagues (2018) found that preschool children had higher levels of attention/persistence when they were enrolled in classrooms where teachers had higher TSE.…”
Section: Variability Of Teacher Self-efficacymentioning
confidence: 99%
“…The vast majority of archival research on teachers’ TSE has focused on teachers of school-age children (for a review, see Zee & Koomen, 2016), although a limited number of studies have examined ECE teachers’ TSE (Chung et al, 2005; Guo et al, 2010, 2011, 2014; Justice et al, 2008; Rhoad-Drogalis et al, 2018; Todd Brown, 2005). Overall, ECE teachers generally have moderately high-to-high TSE, which may not be surprising, given that teachers who teach younger school-age children report higher TSE than teachers of older students (Klassen & Chiu, 2010; Wolters & Daugherty, 2007).…”
Section: Self-efficacy Of Early Childhood Education (Ece) Teachersmentioning
confidence: 99%
See 2 more Smart Citations